Walter J. Ong, Charles Taylor, and the Age of Romanticism - Farrell, Thomas J. (New Explorations)

(untitled) (New Explorations Association, 2024)
In my 20,762-word essay, I present an ambitious account of the life and work of the American Jesuit Renaissance specialist and cultural historian and pioneering media ecology theorist Walter J. Ong (1912-2003; Ph.D. in English, Harvard University, 1955). In addition, I succinctly highlight two books by the Canadian Catholic philosopher Charles Taylor (born in 1931; doctorate in philosophy, Oxford University, 1961): (1) The Language Animal: The Full Shape of the Human Linguistic Capacity (2016); and (2) Cosmic Connections: Poetry in the Age of Disenchantment (2024) – both published by Belknap Press of Harvard University Press. In my discussion of Taylor’s new 2024 book Cosmic Connections, I especially highlight his chapters on Gerard Manley Hopkins and T. S. Eliot. In the text of my lengthy essay (pp. 1-44), I frequently list related works of interest. I hope that you feel the force of my associations. In any event, my alphabetized list of “References” at the end of my essay is rather lengthy (pp. 45-56).